Tinjauan Kebijakan Restrukturisasi Kredit Perbankan Pada Masa Pandemi Covid-19 - Muhammad Jamil Karim (2021)
The emergence of natural disasters that have an impact on a national and even international scale causes all aspects of the field in every country in the world to experience limitations. One example of a natural disaster that has a tremendous impact on the country's economy today is the Covid-19 pandemic. Therefore, these business people have difficulty paying off the loans they have made during the Covid-19 pandemic. This is the background for the author to conduct a review of what policies have been issued by the government in order to provide a credit restructuring stimulus during the Covid-19 pandemic in the banking sector in Indonesia. This final project was prepared with the aim of knowing and conducting a review of the Indonesian banking credit restructuring policy during the Covid-19 pandemic issued by the Financial Services Authority. Based on the results of data processing, the number of debtors whose loans are restructured continues to grow every month. Although since September 2020 the growth has been sluggish, further policies related to credit restructuring are still needed. Based on this, the Regulation of the Financial Services Authority of the Republic of Indonesia Number 48 / POJK.03/2020 was issued.